Learning from the Wisdom of The Prophets: Spiritual Intelligence of Hūd and Muḥammad in Ibn Arabi’s View - Andi Herawati (Universitas Islam Negeri Mataram, 2016)
The wisdom of the prophets in Ibn ‘Arabi’s Fuṣūṣ al-Ḥikam is deeply concerned with discovering how the prophets who are taken up in each chapter exemplify different facets of the deeper spiritual process of the divine-human relation. This article examines two particular fass and wisdom of Hūd and Muḥammad. The wisdom of Hud represents knowledge through the feet” (‘ilm al-rijl), the knowing that can only come through actually traveling through all the tests and lessons of the earthly human existence or sulūk, while the wisdom of Muḥammad defines the role of love and its multiple layers. Both are seen to be a spiritual intelligence of the prophets. Spiritual Intelligence empowers people to deal with and resolve life-world issues while demonstrating virtuous behaviour such as humility, compassion, gratitude, and wisdom. For Ibn ‘Arabī, spiritual intelligence is about discovering intrinsic distinctions between truth and illusion, and spiritual discernment is all about. Finally, through his particular work, Ibn ‘Arabī highlights and assumes a recurrent progression from habitual conditioning that human usually encounter to a greater depth and breadth of consciousness. DOI: http://dx.doi.org/10.20414/ujis.v20i2.821